Peri-implant soft tissue colour around titanium and zirconia abutments: a prospective randomized controlled clinical study - Cosgarea, Raluca; Gasparik, Cristina; Dudea, Diana; Culic, Bogdan; Dannewitz, Bettina; Sculean, Anton (Clinical oral implants research, 2015)
Objectives To objectively determine the difference in colour between the peri-implant soft tissue at titanium and zirconia abutments. Materials and methods Eleven patients, each with two contralaterally inserted osteointegrated dental implants, were included in this study. The implants were restored either with titanium abutments and porcelain-fused-to-metal crowns, or with zirconia abutments and ceramic crowns. Prior and after crown cementation, multi-spectral images of the peri-implant soft tissues and the gingiva of the neighbouring teeth were taken with a colorimeter. The colour parameters L*, a*, b*, c* and the colour differences ΔE were calculated. Descriptive statistics, including non-parametric tests and correlation coefficients, were used for statistical analyses of the data. Results Compared to the gingiva of the neighbouring teeth, the peri-implant soft tissue around titanium and zirconia (test group), showed distinguishable ΔE both before and after crown cementation. Colour differences around titanium were statistically significant different (P = 0.01) only at 1 mm prior to crown cementation compared to zirconia. Compared to the gingiva of the neighbouring teeth, statistically significant (P < 0.01) differences were found for all colour parameter, either before or after crown cementation for both abutments; more significant differences were registered for titanium abutments. Tissue thickness correlated positively with c*-values for titanium at 1 mm and 2 mm from the gingival margin. Conclusions Within their limits, the present data indicate that: (i) The peri-implant soft tissue around titanium and zirconia showed colour differences when compared to the soft tissue around natural teeth, and (ii) the peri-implant soft tissue around zirconia demonstrated a better colour match to the soft tissue at natural teeth than titanium.
Gesehen am 10.12.2020
First published: 24 June 2014